Genetic aspects of conservation and management of the Eurasian Curlew Numenius arquata - De Jong, Adriaan; Brown, Daniel; Domínguez, Jesús; Düttmann, Heinz; McMahon, Barry J.; Walsh, Grace (2023)
Decades of decline have triggered an AEWA action plan and numerous conservation and management projects across the range of Eurasian Curlew Numenius arquata. Several projects include DNA studies, but more have an untapped potential to collect and analyse DNA. This document intends to promote DNA studies in Eurasian Curlew projects, in particular through pointing out the broad array of useful DNA samples that projects can collect for current and future use, often at low costs and without negatively affecting the birds. The document also provides an overview of DNA analysis methods, and advice on how to fit DNA studies sustainably into socio-economical and ethical frameworks. Additionally, the document contains numerous hands-on practical advice and an extensive reference list. The result is a long text, but we hope its structure helps you to navigate smoothly to the parts of your interest, whatever role you have or plan to play in Eurasian Curlew conservation and management projects.